RELATIONSHIP BETWEEN TEACHER SATISFACTION AND QUALITY EDUCATION AT COLLEGE LEVEL IN RAWAL PINDI DIVISION : A REVIEW PAPER - Khabirr, Sundas; Fatima, Aleen (Dinasti International Journal of Digital Business Management, 2020)
Quality education is the most effective method for the Human development, just as it generates modernization in human growth, keeps the whole nation together and pushes the state to extreme achievement. This research aims to explore the view of teachers in the Rawalpindi Division on quality education and their satisfaction and the relationship between quality education and teacher satisfaction at college level. The study population was all teachers in Govt. Degree Colleges in the District of Rawalpindi. The essence of this study was descriptive and correlational in terms of design. By using simple random sampling techniques, the teachers from the 40 government degree colleges were selected as a sample by following the lottery process. Correlation of Commodity Moment Co-efficient was used for quality education and teacher satisfaction. Descriptive statistics were used to assess the interpretation of the teachers and the mean score was taken. The tools of the research were self-constructed questionnaires for teachers on quality education and adapted scales for teacher satisfaction. This study finds that according to the teachers, quality education exits in colleges and they are also happy. A moderately significant positive association between teacher satisfaction and quality education has been found.